Iconografie d'infanzia nell'"officina della maniera". Il caso Rosso Fiorentino - Franco Cambi (Firenze University Press, 2015)
The history of childhood attributes a significat role to images and especially to iconography in painting. The articles examines the images of Manierism and of Rosso Fiorentino, noting the metamorphosis of cherub and an antinomical view of childhood.